Artificial neural network approach for optimal economic dispatch / Sidratul Hakim Md Kerta - Md Kerta, Sidratul Hakim (2013)
The economic load dispatch plays an important role in the operation of power system, and several models have been used to solve these problems. Several classic approaches, like lambda-iteration and quadratic solution are used to find the economic load dispatch. More recently, the soft computing techniques have received more attention and practice for these applications. This thesis discusses the application of artificial neural networks feed forward back propagation for solving the optimization problems. Data has been taken from published work with the maximum and minimum power limit and cost function. All techniques are implemented in Matlab environment.